2017
DOI: 10.1002/2327-6924.12493
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing by nurse practitioners

Abstract: Background and purpose Nurse practitioners (NPs) in New Zealand have been able to prescribe medicines since 2001; however, little is known about their prescribing practice. This study describes the NPs who prescribe community‐dispensed medicines, the patients, and identifies the most frequently prescribed medications. Methods A retrospective search of the Ministry of Health pharmaceutical collection was completed from 2013 to 2015. NP registration number, patient age, gender, deprivation index, and the name an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…One expert opinion and one case report were found (Hendrix & Wojciechowski, 2005; Riegel et al, 2012). Only two quantitative studies were identified (Kurtzman, 2016; Poot et al, 2017). Finally, two nursing association webpages addressing NPs in family practices were determined (AANP, 2019; CNA, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One expert opinion and one case report were found (Hendrix & Wojciechowski, 2005; Riegel et al, 2012). Only two quantitative studies were identified (Kurtzman, 2016; Poot et al, 2017). Finally, two nursing association webpages addressing NPs in family practices were determined (AANP, 2019; CNA, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…(Abou Malham et al, 2020; Canadian Nurses Association [CNA], 2017;Housden et al, 2016;Irving, 2015;Roots & MacDonald, 2014), New Zealand(King et al, 2018;Poot et al, 2017),Steinbrüchel-Boesch et al, 2017). A case study design was used by three authors(Abou Malham et al, 2020;Housden et al, 2016; …”
mentioning
confidence: 99%
“…Training is essential in order to protect midwifery practice and, ultimately, patient care. Appropriate training to extend nurses' skills is considered in leading countries (23). Although the majority of nurses and midwives' decisions are clinically appropriate, continuing education and evaluating prescriptive performance, especially in relation to drugs and interactions, are needed to achieve the most appropriate and safe administration (24).…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, 4.2% of ANPs were reported as working predominantly in mental health settings (American Association of Nurse Practitioners [AANP], 2019), with such roles being more numerous in areas with low numbers of psychiatrists (Feldman et al, 2003;Goolsby, 2011). In Australia, surveys have indicated a low proportion of mental health-focused nurse prescribers (Buckley et al, 2013;Fong et al, 2020), whereas in New Zealand, a study identified less than 1% of patients receiving nurse prescribing were mental health/substance misuse service users (Poot et al, 2017).…”
Section: Nurse Prescribing Internationallymentioning
confidence: 99%